Manganese(I)-Catalyzed Selective Functionalization of Alkynes - Yan, Zhongfei; Zhu, Chengjian; Xie, Jin (Synlett, 2019)
Mn(I)-catalyzed selective functionalization of alkynes permits the convenient synthesis of substituted alkenes with high step and atom economies. Although the insertion of five-membered chelated manganacycle intermediates into alkynes has been widely reported, nonchelated Ar–Mn(I) species originating from commercially available arylboronic acids are unprecedented. Our new protocol achieved a challenging hydroarylation of unsymmetrical 1,3-diynes with arylboronic acids with complete regio-, stereo-, and chemoselectivity to give a wide array of trisubstituted conjugated (Z)-enynes in moderate to good yields.
Keywords: arylboronic acids; alkynes; C–H activation; manganese catalysis; diynes; enynes